Comparison of clinical outcomes following 2 years of treatment of first-episode psychosis in urban early intervention services in Canada and India. (September 2020) - Malla, Ashok; Iyer, Srividya N.; Rangaswamy, Thara; Ramachandran, Padmavati; Mohan, Greeshma; Taksal, Aarati; Margolese, Howard C.; Schmitz, Norbert; Joober, Ridha
Abstract : Background: Purported superior outcomes for treatment of psychosis in low- and middle-income (LMICs) compared with high-income (HICs) countries have not been examined in the context of early intervention services (EIS). Aims: To compare 2-year clinical outcomes in first-episode psychosis (FEP) treated in EIS in Chennai (LMIC) and Montreal (HIC) using a similar EIS treatment protocol and to identify factors associated with any outcome differences. Method: Patients with FEP treated in EIS in Chennai ( n = 168) and Montreal ( n = 165) were compared on change in level of symptoms and rate and duration of positive and negative symptom remission over a 2-year period. Repeated-measures analysis of variance, and logistic and linear regression analyses were conducted. Results: Four patients died in Chennai compared with none in Montreal. Family support was higher for Chennai patients ( F = 14.05, d.f. = 1, P < 0.001, ƞp 2 = 0.061) and increased over time at both sites ( F = 7.0, d.f. = 1.915, P < 0.001, ƞp 2 = 0.03). Negative symptom outcomes were significantly better in Chennai for level of symptoms (time × site interaction F = 7.36, d.f. = 1.49, P = 0.002, ƞp 2 = 0.03), duration of remission (mean 16.1 v . 9.78 months, t = −7.35, d.f. = 331, P < 0.001, Cohen's d = 0.80) and the proportion of patients in remission (81.5% v . 60.3%, χ 2 = 16.12, d.f. = 1, P < 0.001). The site differences in outcome remained robust after adjusting for inter-site differences in other characteristics. Early remission and family support facilitated better outcome on negative symptoms. No significant differences were observed in positive symptom outcomes. Conclusions: Patients with FEP treated in EIS in LMIC contexts are likely to show better outcome on negative symptoms compared with those in HIC contexts. Early remission and family support may benefit patients across both contexts.